Caracterização da aquicultura ornamental na Zona da Mata Mineira - Renato Silva Cardoso (2011)
Globalization has brought changes in ornamental fish trade as well as an increase in market opportunities. According to the Food and Agriculture Organization of the United Nations the average growth of international trade in ornamental fish has been 14% per year since 1985. Brazil is one of the leading exporters of ornamental fish, not in terms of quantity and value but in terms of biodiversity. Most of the imported and exported freshwater and saltwater ornamental fish are collected from the wild. However, in spite of advances in the ornamental fish production, many Brazilian producers still have not adopted good methods of production. They need the assistance of the Brazilian government in order to the country to become an exporter-producer instead of an exporter-extractor